Handbook on Participatory Methods for Community-Based Projects: A Guide for Programmers and Implementers Based on the Participatory Action Research Project with Young Mothers and their Children in Liberia, Sierra Leone, and Northern Uganda - Onyango, Grace; Worthen, Miranda (PAR Project, 2010)
Participation” is a word that has been used in child protection and development circles for many years. The term has come to mean everything from a token consultation with a benefi ciary group to full-scale participation by affected ommunities in program development, implementation, and evaluation. In this handbook, we will be describing methods at this further end of the spectrum – that is, highly participatory approaches. Participatory Action Research (PAR) is one type of participatory methodology that is designed not only to achieve social change for a group or in a community, but also to document and learn from that process through research. PAR actively involves the target participants in a process to improve their situations. Participants become the “program designers” and “researchers” as they identify and implement solutions to the obstacles to achieving full participation in their community. Participants are key actors as evaluators of the project, refl ecting on how well the process has helped them reach their stated goals. This process whereby participants engage in self-refl ective inquiry into their own situations, identify problems and possible solutions, implement the solutions, and evaluate the project is an iterative one – as new problems or obstacles are recognized, approaches to addressing the problems are developed and implemented. Unlike traditional program design that is agency-centric where a problem is identifi ed, then a program is implemented, and after implementation, the program is evaluated, PAR offers multiple opportunities to develop and build upon what is learned throughout the process of implementation with the participants taking center stage.
Keywords: Community-Based Projects; Participatory Action Research Project; Young Mothers; Children